Confrontations Between Theists and Atheists - Kowalski, Ludwik (Filozoficzne Aspekty Genezy, 2021)
The commentary focuses on Gould’s idea of NOMA, according to which science and theology are two Non-Overlapping Magisteria. The term “non-overlapping” is appropriate because methods of validation of claims in these two fields of intellectual investigation. are different, not because the areas of investigation should be different. The author was once an active atheist, in Poland; now he is a practicing theist, belonging to a Reform synagogue in the United States. He thinks that Gould’s idea, if universally accepted, could help to reduce intensity of dangerous doctrinal confrontations between theists and atheists, and between different groups of theists. The commentary ends by a quote from a statement about desirable collaboration between religion and science, made by Pope John Paul.